Balancing Load in a Computational Grid Applying Adaptive, Intelligent Colonies of Ants - Salehi, M.A.; Deldari, H.; Dorri, B.M. (Informatica)
Balancing Load in a Computational Grid Applying Adaptive, Intelligent Colonies of Ants